Tracing Empirical Trails of Schumpeterian Development - Michael Peneder (Austrian Institute of Economic Research (WIFO), 2004)
Schumpeterian development is characterised by the simultaneous interplay of growth and qualitative transformations of the economic system. At the sectoral level, such qualitative transformations become manifest as variations in the sectoral composition of production. Following the implementation of Harberger's method of visualising the impact of differential productivity growth, dynamic panel estimations are applied to a standard growth model modified to include specific structural variables for both the manufacturing and the services sectors. Covering 28 countries over the period between 1990 and 2000, the results give empirical substance to the evolutionary emphasis on Schumpeterian development as opposed to mere aggregate growth.
Keywords: O11; O30; O41; 330; Structural change; economic growth; Schumpeterian development; evolutionary economics; Strukturwandel; Wirtschaftswachstum; Evolutionsökonomik; Schätzung; Welt; Schumpeterismus